REDUCTION OF ZEBRA CHIP INFECTION SYMPTOMS IN POTATO - Ricardo Martinez-Gutierrez; Martha Elena Mora Herrera; Carlos Trejo; Isidro Humberto Almeyda-Leon; Humberto Antonio Lopez-Delgado (Tropical and Subtropical Agroecosystems)
Background: There have been few studies on the long-term effects of hydrogen peroxide and dehydroascorbate (H2O2 and DHA) on biotic stress, especially in potato plants infected with Candidatus Liberibacter solanacearum (Lso) that cause the Zebra chip disease, characterized by browning of the tubers, reduced productivity and anomalies in the morphology of the plant. Objective: To evaluate the long-term effects of DHA and H2O2 treatments on the reduction of symptoms in potato plants infected with Lso. This research was realized at the INIFAP facilities at Experimental Site Metepec, Mexico State. Methodology: Single nodes were waterlogged in DHA, H2O2, or distilled water, followed by culture in Murashige and Skoog medium (MS), and microplants obtained were transplanted in greenhouse conditions. Seventy-three days after transplanting, leaf water potential (Yw), chlorophyll, H2O2 content, and catalase activity (CAT) were determined. Results: DHA significantly increased minituber weight and chlorophyll content in the long term. It also, reduced H2O2 content and increased CAT in infected plants, resulting in increased minituber weight. A long-term effect of H2O2 was observed, as it induced significant increases in stem height, shoot fresh and dry weight, relative chlorophyll content, and minituber weight. Implications: DHA and H2O2 participated as signal molecules, triggering physiological changes promoting increases in productivity in plants infected with Lso, justifying the importance of the study of these molecules under biotic stress conditions. Conclusion: Long-term effects of H2O2 and DHA on the amelioration of symptoms of potato Zebra chip associated with Lso solanacearum were demonstrated.